Passenger - Bracken, Alexandra (Los Angeles, 2016)
"Two worlds collide in this sweeping, romantic novel about a love that crosses centuries by bestselling author of the Darkest Minds series, Alexandra Bracken"--
Keywords: Time travel -- Juvenile fiction; Ocean travel -- Juvenile fiction; Violinists -- Juvenile fiction; Romance fiction; Action and adventure fiction